Prospective study on central venous line associated bloodstream infections. Issue 9 (2nd June 2011) - Wagner, Mine; Bonhoeffer, Jan; Erb, Thomas O; Glanzmann, René; Häcker, Frank Martin; Paulussen, Michael; Weibel, Daniel; Heininger, Ulrich
Abstract : Objective: To prospectively assess the incidence rates and characteristics of central venous line associated bloodstream infections (CLABSI) in one institution. Methods: All patients with indwelling central venous catheters (CVC) between 1 April 2008 and 31 March 2009 were enrolled. The medical records of patients were reviewed and information on relevant characteristics entered into a standardised questionnaire. Central laboratory records were regularly checked for positive blood cultures in study patients. Results: There were 209 CVC for a total of 14752 CVC days in 152 patients (88 males, 58%) including neonates and patients with surgical conditions and haemato-oncological and other underlying diseases. Median age at CVC insertion was 3 months (IQR 0–56 months). Fourteen CLABSI occurred in 13 patients. Overall CLABSI incidence (per 1000 CVC days) was 0.95 (9.71 for silastic percutaneous CVC, 7.65 for other CVC, 1.97 for Broviac, 0.18 for Port-a-cath). CVC remained in place for ≤14 days in 109 (52%) instances, 15–90 days in 45 (22%) instances and >90 days in 55 (26%) instances. The incidence of CLABSI in these three categories was 3.36, 4.36 and 0.47, respectively. Predominating cultured organisms were coagulase-negative staphylococci (N=3), S. aureus (N=3), and Enterococcus spp. (N=3). Conclusions: CLABSI incidence varied by type of catheter and type of patient, with the highest risk in neonates (with silastic percutaneous CVC) and by far the lowest risk for Port-a-cath CVC. Prophylactic measures to reduce CLABSI should be tailored to individual types of catheters and patient characteristics.